Dual-locked enzyme-activatable bioorthogonal fluorescence turn-on imaging of senescent cancer cells - Wang, Xinzhu (2024)
Bioorthogonal pretargeting optical imaging shows the potential for enhanced diagnosis and prognosis. However, the bioorthogonal handles, known for being "always reactive", may engage in reactions at unintended sites with their counterparts, resulting in nonspecific fluorescence activation and diminishing detection specificity. Meanwhile, despite the importance of detecting senescent cancer cells in cancer therapy, current methods mainly rely on common single senescence-associated biomarkers, which lack specificity for differentiating between various types of senescent cells. Herein, we report a dual-locked enzyme-activatable bioorthogonal fluorescence (DEBOF) turn-on imaging approach for the specific detection of senescent cancer cells. A dual-locked bioorthogonal targeting agent (DBTA) and a bioorthogonally activatable fluorescent imaging probe (BAP) are synthesized as the biorthogonal pair. DBTA is a tetrazine derivative dually caged by two enzyme-cleavable moieties, respectively, associated with senescence and cancer, which ensures that its bioorthogonal reactivity ("clickability") is only triggered in the presence of senescent cancer cells. BAP is a fluorophore caged by trans-cyclooctane (TCO), whose fluorescence is only activated upon bioorthogonal reaction between its TCO and the decaged tetrazine of DBTA. As such, the DEBOF imaging approach differentiates senescent cancer cells from nonsenescent cancer cells or other senescent cells, allowing noninvasive tracking of the population fluctuation of senescent cancer cells in the tumor of living mice to guide cancer therapies. This study thus provides a general molecular strategy for biomarker-activatable in vivo bioorthogonal pretargeting imaging with the potential to be applied to other imaging modalities beyond optics.